Photocatalysts for Organics Degradation - Bonelli, Barbara; Manzoli, Maela; Freyria, Francesca S.; Esposito, Serena (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The quality of water is not only a technological and scientific issue, but a social and economic problem, in both developed and developing countries. Besides local regulations, which differ between regions and need constant upgrades, significant scientific developments are required in both the detection and removal of water contaminants. This Issue focuses on some recent advancements in the photocatalytic removal of organic pollutants, which is one of the aspects of the problem that involves the need of advanced catalysts and implies significant advancements in the field of materials science and chemical engineering.